IMPROVING STUDENTS LEARNING EXPERIENCE USING DANCE REVO IN TEACHING TINIKLING AMONG GRADE 6 PUPILS (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study examined the integration of Dance Revo as an interactive instructional tool for teaching the traditional Tinikling dance to Grade 6 students. It aimed to improve students' comprehension of choreography, timing, coordination, and footwork, while also encouraging active engagement, cultural appreciation, and collaborative learning. By blending traditional Filipino dance with modern technology, the study sought to create a more engaging, innovative, and enjoyable learning experience. A quantitative research design was utilized to examine student engagement, skill enhancement, and learning outcomes. Data were collected through surveys and observational assessments. Grade 6 students participated in Tinikling dance sessions using the Dance Revo platform, and their progress was systematically evaluated through structured performance assessments and feedback, focusing on choreography, coordination, and overall participation. The results of the study demonstrate that integrating Dance Revo into Tinikling instruction positively influenced the performance of Grade 6 students. This was evident through notable shifts in the percentage distribution between pre-test and post-test scores. Significant improvements were recorded in specific categories, such as Category 2 (from 4.95% to 11.73%) and Category 7 (from 5.89% to 12.13%), indicating increased engagement and skill acquisition. Although a decline was observed in Category 5 (from 13.25% to 4.30%), this likely reflects a redistribution of students toward higher performance levels. Overall, the findings suggest that the use of interactive tools like Dance Revo enhances students’ learning experiences by improving rhythm, coordination, and memory retention. Moreover, it promoted peer collaboration, encouraged creativity, and contributed to a more positive and dynamic classroom environment. The study concludes that incorporating interactive technology into traditional dance instruction, such as the use of Dance Revo in teaching Tinikling, effectively enhances student engagement, understanding, and skill development. This approach not only supports the mastery of choreography and coordination but also fosters cultural appreciation in a more engaging and accessible manner. It is therefore recommended that educators integrate digital tools into cultural dance education to create a more dynamic, enjoyable, and inclusive learning environment.
Keywords: dance revo; tinikling; interactive technology; traditional dance; cultural education; student engagement; choreography; rhythm; coordination; digital tools; grade 6 learners; multimedia learning